2007
DOI: 10.1073/pnas.0607745104
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in prion protein oligomerization pathways results from domain expansion as revealed by hydrogen/deuterium exchange and disulfide linkage

Abstract: The prion protein (PrP) propensity to adopt different structures is a clue to its biological role. PrP oligomers have been previously reported to bear prion infectivity or toxicity and were also found along the pathway of in vitro amyloid formation. In the present report, kinetic and structural analysis of ovine PrP (OvPrP) oligomerization showed that three distinct oligomeric species were formed in parallel, independent kinetic pathways. Only the largest oligomer gave rise to fibrillar structures at high conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
145
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(164 citation statements)
references
References 32 publications
17
145
2
Order By: Relevance
“…This opening mechanism illustrated in Figure 4c implies a conformational change in the S2-H2 hingeloop corresponding to residues 168-173. Altogether kinetic and structural data reported by Eghiaian et al are consistent with observations related to the PrP C /PrP Sc conversion in vivo [33]. The conformation of the S2-H2 loop seems to play an important role in PrP C /PrP Sc conversion.…”
Section: Structural Dynamics Of Prp Conversionsupporting
confidence: 88%
See 1 more Smart Citation
“…This opening mechanism illustrated in Figure 4c implies a conformational change in the S2-H2 hingeloop corresponding to residues 168-173. Altogether kinetic and structural data reported by Eghiaian et al are consistent with observations related to the PrP C /PrP Sc conversion in vivo [33]. The conformation of the S2-H2 loop seems to play an important role in PrP C /PrP Sc conversion.…”
Section: Structural Dynamics Of Prp Conversionsupporting
confidence: 88%
“…4a) [33]. The kinetic investigation showed that PrP can generate different types of oligomers according to a parallel oligomerization pathway (Fig.…”
Section: Structural Dynamics Of Prp Conversionmentioning
confidence: 95%
“…We thus propose that the separation of S1-H1-S2 from the H2H3 bundle in PrP is a prerequisite for misfolding as suggested in Ref. 42 and that exposing or isolating H2H3 is a necessary step in mammalian cells for misfolding and for generation of aggregated PKresistant species.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, electron microscopy has detected a head-to-head disulfide-bonded interaction (11). The structure of pathogenic serpin polymers has thus not been unambiguously resolved, although detailed knowledge of the structure of these polymers is critical for understanding the basis of serpin-linked diseases and for designing effective therapeutics.Hydrogen/deuterium exchange measured by mass spectrometry (HXMS) has proven to be a powerful method for probing the structure and dynamics of proteins and protein assemblies that are not accessible to other techniques, and several recent studies have employed HXMS to gain insight into the structural organization of amyloid fibrils (12)(13)(14). HXMS provides information on dynamics and solvent accessibility throughout the entire structure of a protein and does not require the attachment of exogenous labels (15).…”
mentioning
confidence: 99%
“…Hydrogen/deuterium exchange measured by mass spectrometry (HXMS) has proven to be a powerful method for probing the structure and dynamics of proteins and protein assemblies that are not accessible to other techniques, and several recent studies have employed HXMS to gain insight into the structural organization of amyloid fibrils (12)(13)(14). HXMS provides information on dynamics and solvent accessibility throughout the entire structure of a protein and does not require the attachment of exogenous labels (15).…”
mentioning
confidence: 99%